International model of science policy: from the rhetoric of innovation to the imperative of competitiveness - Chávarro, Luis Alfonso (2023)
After the linear model of science policy had been in force, a model centered on the economics of innovation and competitiveness began to take shape in the 1960s and, by the 1980s, it had materialized in scripts that were rapidly disseminated and appropriated in many countries of the Western world. Its conceptual sources are to be found in the ideas of economists of the stature of Schumpeter, Smith and Ricardo, but once reworked in the management literature, they were socialized in the spheres of decision-making on the generation of scientific knowledge. This model, centered on economic innovation, privileges applied research over basic research, to the detriment of other forms of innovation such as social, artistic and environmental. Its rapid assimilation into the scientific policy guidelines of Latin American countries reveals a phenomenon of diffusion by imitation rather than by reflection on the true capabilities of the countries, and this has given rise to a mimetic isomorphism of institutions, systems and research practices, far removed from the issues of relevant research needs. Thus, after the 2020 pandemic, the precariousness of the research that this model has led to in the Latin American context has become evident.